2006
DOI: 10.1016/j.stam.2006.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduction–oxidation treatment on the catalytic activity over tin oxide supported platinum catalysts

Abstract: In precious metal-oxide catalyst system, the support materials strongly affect the catalytic activity. Especially the term of strong metal-support interaction is well known: Tauster . It was also demonstrated that this interaction could modify the catalytic activity of precious metals in different reactions. Accordingly, elucidating these phenomena will be the useful guide for the development of new class of active catalysts. Thus, we had focused on the chemical interaction between platinum and oxide and repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Even though the SMSI can enhance catalyst stability, it can also cause local structural changes that can decrease catalyst reactivity [4][5][6][7]. A wide variety of experiments have been performed on different metal-oxide supports, including TiO x , CeO x , VO x , SnO x , and AlO x to assess if and how these oxides can improve the stability of noble metal catalysts, including Pt, Au, Ag, and Pd [8][9][10][11]. Platinum is commonly used as catalysts for industrial applications as well as for academic research [1][2][3][4][5][6]12].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the SMSI can enhance catalyst stability, it can also cause local structural changes that can decrease catalyst reactivity [4][5][6][7]. A wide variety of experiments have been performed on different metal-oxide supports, including TiO x , CeO x , VO x , SnO x , and AlO x to assess if and how these oxides can improve the stability of noble metal catalysts, including Pt, Au, Ag, and Pd [8][9][10][11]. Platinum is commonly used as catalysts for industrial applications as well as for academic research [1][2][3][4][5][6]12].…”
Section: Introductionmentioning
confidence: 99%
“…Tin oxide (SnO 2 ), with n-type semiconducting property and good electrochemical stability, has been proposed as a potential catalyst support material for fuel cell application [10][11][12][13][14][15][16][17][18]. Previous studies have shown that SnO 2 can promote the electro-oxidation of CO, methanol, and ethanol due to the formation of OH species at low potentials and the strengthened metal-support interaction [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Tin dioxide is an n-type semiconductor with a wide band gap (3.6 eV) and rutile bulk structure [13]. In the past decades, SnO 2 has attracted much attention for its various applications in catalysis, gas sensing, rechargeable Li battery and optical electronic devices [13][14][15][16]. It should be marked that SnO 2 is one of the most widely used semiconductor oxides for the manufacturing of sensors applied in the environment monitoring [17].…”
Section: Introductionmentioning
confidence: 99%